The Implementation of the Hidden Object Interactive Game Using Powerpoint in Improving Students' Vocabulary Mastery - Nanda Triana; Amra Ariyani; La Sunra (PT ARRUS Intelektual Indonesia, 2023)
This research aims to find out whether the implementation of the Hidden Object interactive game using PowerPoint can improve students' vocabulary mastery or not. A quantitative pre-experimental research type was used in this study. All seventh-grade students at SMP Negeri 1 Watansoppeng made up the population of this study. The sample was taken by selecting one class randomly as a representative of a cluster (cluster random sampling) of 25 students. The instrument used was the vocabulary test while data collection was carried out using pretest, treatment, and posttest techniques. Descriptive statistical analysis was the technique of data analysis that was applied where the average pretest score of the 25 students in this study was 72.84, and the average posttest score was 87.84. In addition, it is evident that the two-tailed significance value in the pretest and posttest results was 0.000 which denotes that the two-tailed value is less than 0.05 (significant level), and based on decision-making, this indicates that H0 is rejected while H1 is accepted. In addition, the analysis results obtained from each aspect of vocabulary, namely: meaning has a mean pretest and posttest difference of 19.40, spelling, 11.72, pronunciation 3.32, word classes, 1.52 and word use has a mean difference of 43.04. Other results also show that there were four aspects of vocabulary, namely meaning, spelling, pronunciation, and word use which can show that the two-tailed value was less than 0.05 while the value for the two-tailed aspect of word classes was more than 0.05. It is stated that the four aspects of vocabulary other than Word Classes reject H0 while H1 is accepted. This means that there is a significant difference between student scores before and after implementing the Hidden Object interactive game using PowerPoint. Thus, it can be inferred that in general the implementation of the Hidden Object interactive games using PowerPoint significantly improves students' vocabulary mastery. But for each aspect of vocabulary, only word classes had the smallest mean difference and did not have a significant improvement in students' vocabulary while the biggest mean difference was in the word use aspect.